Internal triplication in the structure of human ceruloplasmin. - Takahashi, N (1983)
Amino acid sequence analysis of the 67,000-dalton (67-kDal) fragment that is the amino-terminal half of human ceruloplasmin has revealed internal triplication in the primary structure of the entire molecule. This is illustrated by comparison of 620 residues representing homologous domains of the 67-kDal fragment and of the 50-kDal and 19-kDal fragments that together comprise the carboxyl-terminal half of the molecule. The polypeptide chain is divided into three covalently linked homologous segments, each of about 340 residues. All three homology units have about 30% identity in sequence, and each pair exhibits at least 40% identity. The statistical significance of the 3-fold internal duplication was established by computerized analysis of the sequence. These results and studies of the sites of limited proteolytic cleavage support a model for the ceruloplasmin molecule consisting of an alternating structure of six domains of two different kinds (or possibly nine domains of three kinds). The 3-fold internal homology suggests that the ceruloplasmin molecule evolved by tandem triplication of ancestral genes.